Taqyīm Ta‘līm al-Lugah al-‘Arabiyyah bi Ṭarīqah al-Ikhtibār fī Māddat al-Adab al-‘Arabī - Ulfi Usykuriyah Khoiry (KURAS Institute, 2026)
The students' understanding of the lesson is a sign of the success of education, and one way to determine the success of students after the learning process is to evaluate the test. The test has specific goals and conditions with special rules. The use of tests in Arabic literature is different from other language tests because the process of literature in teaching Arabic is connected to the taste of language. It is clear that the method of this research is library research with data sources related to tests in literature. This research takes primary data from the book